2022
DOI: 10.1007/s10311-022-01458-1
|View full text |Cite
|
Sign up to set email alerts
|

Algal biomass valorization for biofuel production and carbon sequestration: a review

Abstract: The world is experiencing an energy crisis and environmental issues due to the depletion of fossil fuels and the continuous increase in carbon dioxide concentrations. Microalgal biofuels are produced using sunlight, water, and simple salt minerals. Their high growth rate, photosynthesis, and carbon dioxide sequestration capacity make them one of the most important biorefinery platforms. Furthermore, microalgae's ability to alter their metabolism in response to environmental stresses to produce relatively high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(44 citation statements)
references
References 222 publications
0
44
0
Order By: Relevance
“…In the USA, a model study confirmed that pure CO 2 from the corn ethanol production process could be used for algae cultivation in an open pond, thus reducing GHG emission and water stress and can avoid the energy-intensive carbon capturing process for CCU (68). A wide range of value-added products for industrial applications can also be produced from algae-based biomass, such as food, feed and cosmetics (69). It seems that algae have a promising future not only for removing atmospheric CO 2 but also can play an important role in producing food, feed and biofuels.…”
Section: Seaweed/algaementioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, a model study confirmed that pure CO 2 from the corn ethanol production process could be used for algae cultivation in an open pond, thus reducing GHG emission and water stress and can avoid the energy-intensive carbon capturing process for CCU (68). A wide range of value-added products for industrial applications can also be produced from algae-based biomass, such as food, feed and cosmetics (69). It seems that algae have a promising future not only for removing atmospheric CO 2 but also can play an important role in producing food, feed and biofuels.…”
Section: Seaweed/algaementioning
confidence: 99%
“…68 A wide range of value-added products for industrial applications can also be produced from algae-based biomass, such as food, feed and cosmetics. 69 It seems that algae not only have a promising future for removing atmospheric CO 2 but also can play an important role in producing food, feed and biofuels.…”
Section: Seaweed/algaementioning
confidence: 99%
“…Such efficient sequestration of carbon by microalgae can theoretically generate ∼65 million tons of biofuel, costing around $8.52/gallon . On average, microalgal farming in an open/closed system can utilize ∼513 tons of CO 2 to generate ∼280 tons of dry biomass/hectare annually . Such carbon fixation efficacy of microalgal cells not only provides biomass/biofuels but also has greener prospects of remediating industrial flue gases that are rich in CO 2 .…”
Section: Microalgae As An Efficient Model For Capturing Carbon and Pr...mentioning
confidence: 99%
“…For example, with the aeration level of 10–20% CO 2 , Chaetoceros muelleri achieved high lipid productivity of 51 mg L –1 day –1 . Other marine strains, such as Nannochloropsis sp., Isochrysis sp., Chlorella salina, Pavlova salina, etc., having oil-rich biomass, have also been explored for their adaptability to varying amounts of CO 2 . Further, the species ability to fix CO 2 and produce bioenergy is primarily dependent upon the specificities of the microalgal physiology and the environmental conditions.…”
Section: Microalgae As An Efficient Model For Capturing Carbon and Pr...mentioning
confidence: 99%
“…The use of biomass wastes as starting materials has sparked intense research interest due to their physiochemical stability, light weight, low cost, and environmental friendliness (Aslam et al 2021). Oil palm biomass is an efficient source of carbon for conversion to high-value products especially palm kernel shells (PKS) as activated carbon precursors (Norrrahim et al 2022;Sarwer et al 2022). The high carbon percentage in PKS is promising for the production of activated carbon (AC), as it contributes to a high product yield.…”
Section: Introductionmentioning
confidence: 99%